THE CHALLENGES OF APPRENTICESHIP: THE STATUS QUO OF PROFESSIONAL MASTERS’ PEDAGOGICAL COMPETENCIES - Ciuciulkiene, Nijole; Tandzegolskiene, Ilona; Stupelienė, Gita Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
With the emerging of apprenticeship (work-based learning form) in Lithuania, an important role is played by professional masters, who are monitoring young specialists' professional practice, form their professional skills, develop a well-oriented and skillful specialist. The main aim of this research is to analyze the development of pedagogical competencies of professional masters during work-based learning process. The qualitative research data were gathered during semi-structured interview. Twelve professional vocational masters from different Lithuanian vocational schools participated in the research. The performed thematic content analysis findings showed that the competencies of the professional vocational masters actively develop, grow, and change mainly through interaction with students in the process of work-based learning, when supervising practice masters become counselors, guardians, consultants, and inspirers. The most significant challenges include transferring subject knowledge to students, their motivation, and work with students with special needs. The results reveal that vocational practice masters need to improve their pedagogical competencies and psychological knowledge, which would help students to convey knowledge of the profession and motivate them to learn.